The Territorial Foundations of the Sovereign State in East Asia - Douglas R. Howland (The Journal of Transcultural Studies, 2018)
European incursions into Asia created Asian awareness of territorial sovereignty by its very violation. The bilateral treaties that Japan and China signed with European and American states in the nineteenth century made explicit the centrality of territory in the modern state form, for these treaties created a regime of extraterritoriality that exempted foreign residents from the jurisdiction of the local state. Only when China or Japan had secured its territorial jurisdiction could it assert a sovereign standing in the world order, and two processes were key: Japan and China had to consolidate their respective territories, lest foreign powers claim proximate footholds that could become security threats. And each needed to possess the legal and political organization that would render each state capable of imposing jurisdiction within its own territory.